Intracranial aneurysm treatment with intrasaccular flow disruption: comparison of WEB-21 and WEB-17 systems. (5th October 2021) - Pagano, Paolo; Paiusan, Laurentiu; Soize, Sebastien; Pierot, Laurent
Abstract : Background: New generations of Woven EndoBridge (WEB) devices (WEB-21 and WEB-17) are available to treat aneurysms with a width <6.5 mm. Limited comparisons between both systems exist in the literature, but mid-term efficacy has not been compared. Our study aimed to compare the indications, feasibility, and safety of both systems and to evaluate their efficacy at mid-term follow-up (12 months). Methods: Aneurysms treated with WEB-21 and WEB-17 were extracted from a prospective database. Patient and aneurysm characteristics, complications, and anatomical results were analyzed by an interventional neuroradiologist, independent of the procedures. Results: From June 2015 to November 2019, 87 patients with 92 aneurysms were treated with WEB-21 (38/92, 41.3%) and WEB-17 (54/92, 58.7%). WEB-21 and WEB-17 had high treatment feasibility (97.4% and 94.4%, respectively). A higher percentage of ruptured aneurysms were treated with WEB-17 (9.3%) than with WEB-21 (2.6%; p=0.03). Morbidity and mortality at 1 month were similar in both groups (no morbidity in either group, and mortality 2.7% in the WEB-21 group and 2.0% in the WEB-17 group). The rate of complete and adequate aneurysm occlusion was not significantly higher with the WEB-17 system (59.2% and 95.9%, respectively) compared with the WEB-21 (52.9% and 85.3%, respectively). Conclusions: This study showed the high feasibility of aneurysm treatment with both the WEB-21 and WEB-17 systems. Indications were relatively similar with both devices except for ruptured aneurysms, which were more frequently treated with the WEB-17 device. Efficacy at 12 months (complete and adequate occlusions) was slightly, but not significantly, better with the WEB-17 device.